2018
DOI: 10.1152/ajpheart.00536.2017
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-dependent impairment of α2-adrenergic autoreceptor inhibition of Ca2+channels in sympathetic neurons from DOCA-salt but not high-fat diet-induced hypertensive rats

Abstract: DOCA-salt and obesity-related hypertension are associated with inflammation and sympathetic nervous system hyperactivity. Prejunctional α-adrenergic receptors (αARs) provide negative feedback to norepinephrine release from sympathetic nerves through inhibition of N-type Ca channels. Increased neuronal norepinephrine release in DOCA-salt and obesity-related hypertension occurs through impaired αAR signaling; however, the mechanisms involved are unclear. Mesenteric arteries are resistance arteries that receive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…Few studies have investigated the macrophage-nerve relationship in the mesenteric vasculature. Studies in a rat model of hypertension found that CD163+ macrophage accumulation in the mesenteric artery adventitia is linked to increased blood pressure through macrophage-derived oxidate stress acting on ganglionic neuronal alpha-2 adrenergic receptors (37). In that study, clodronate-based macrophage depletion acted to lower blood pressure by preserving neuronal alpha-2 receptor function.…”
Section: Adventitial Nerve-macrophage Signaling In Ibdmentioning
confidence: 85%
“…Few studies have investigated the macrophage-nerve relationship in the mesenteric vasculature. Studies in a rat model of hypertension found that CD163+ macrophage accumulation in the mesenteric artery adventitia is linked to increased blood pressure through macrophage-derived oxidate stress acting on ganglionic neuronal alpha-2 adrenergic receptors (37). In that study, clodronate-based macrophage depletion acted to lower blood pressure by preserving neuronal alpha-2 receptor function.…”
Section: Adventitial Nerve-macrophage Signaling In Ibdmentioning
confidence: 85%
“…This could be related to the relative role of the autonomic nervous system in BP regulation in the various models we studied. For example, although baroreflex impairment and neurogenic mechanisms contribute to the BP differences between Dahl SS rats on different salt intakes ( 42 ), autonomic nervous system abnormalities appear to play no role in high-fat diet–induced hypertension in Dahl SS rats ( 43 45 ). This is in contrast to the SHR, where autonomic factors clearly are important for the maintenance of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the responsiveness of the postsynaptic α 1 adrenergic receptor is the same in both groups, and sympathetic nervous responsivity to PNS is suppressed in DOCA‐salt rats compared to that in sham rats. According to recent studies, dysfunction of α 2 adrenergic receptors and adenosine A 1 receptors in the superior mesenteric and celiac ganglia of DOCA‐salt rats is related to the augmentation of the sympathetic reaction. Research suggests that the increase in sympathetic nerve excitation and the increased responsiveness of the vascular α 1 adrenergic receptor were associated with vascular constriction in the aorta or veins in DOCA‐salt rats.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, dysfunction of α 2 adrenergic receptors 23 and adenosine A 1 receptors 24 in the superior mesenteric and celiac ganglia of DOCA-salt rats is related to the augmentation of the sympathetic reaction. Research suggests that the increase in sympathetic nerve excitation and the increased responsiveness of the vascular α 1 adrenergic receptor were associated with vascular constriction in the aorta 25 or veins 26 in DOCA-salt rats.…”
Section: Discussionmentioning
confidence: 99%